2005
DOI: 10.1104/pp.104.053637
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Evolutionarily Conserved and Variable Proteins of Arabidopsis Cytosolic Ribosomes  

Abstract: Analysis of 80S ribosomes of Arabidopsis (Arabidopsis thaliana) by use of high-speed centrifugation, sucrose gradient fractionation, one-and two-dimensional gel electrophoresis, liquid chromatography purification, and mass spectrometry (matrix-assisted laser desorption/ionization time-of-flight and electrospray ionization) identified 74 ribosomal proteins (r-proteins), of which 73 are orthologs of rat r-proteins and one is the plant-specific r-protein P3. Thirty small (40S) subunit and 44 large (60S) subunit r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
209
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(223 citation statements)
references
References 89 publications
11
209
0
Order By: Relevance
“…We conclude that the RPL10B protein has a specific and essential participation during plant growth, which cannot be replaced by the other RPL10 proteins. Moreover, the presence of the RPL10B isoform has not yet been confirmed in the Arabidopsis 80S ribosome, as no specific tryptic peptide from this protein has been identified by MS/MS in survey experiments (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). Alternatively, it cannot be ruled out that RPL10B has extraribosomal functions during development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We conclude that the RPL10B protein has a specific and essential participation during plant growth, which cannot be replaced by the other RPL10 proteins. Moreover, the presence of the RPL10B isoform has not yet been confirmed in the Arabidopsis 80S ribosome, as no specific tryptic peptide from this protein has been identified by MS/MS in survey experiments (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). Alternatively, it cannot be ruled out that RPL10B has extraribosomal functions during development.…”
Section: Discussionmentioning
confidence: 98%
“…Identification of proteins from purified ribosomes by two-dimensional (2D) electrophoretic analyses followed by mass spectrometry (MS) demonstrated the presence of 79 families of ribosomal proteins in the 80S ribosome. Nearly half are represented by two or more protein spots on 2D gels, indicating that proteins are posttranslationally modified and/or present as different isoforms (Chang et al, 2005;Giavalisco et al, 2005;Carroll et al, 2008). It is hypothesized that this ribosomal heterogeneity fosters selective translation of specific mRNA under particular cell conditions (Barakat et al, 2001;Szick-Miranda and Bailey-Serres, 2001;Giavalisco et al, 2005;Carroll et al, 2008).…”
mentioning
confidence: 99%
“…2). Proteomic studies of the 80S cytosolic ribosome using different Arabidopsis tissues by 2D electrophoresis followed by spectrometric mass showed that both RPL10A and RPL10C were components of the 60S subunit, while RPL10B was not identified (Chang et al, 2005;Carroll et al, 2008;Turkina et al, 2011). However, our complementation studies in yeast suggest that RPL10B, as well as RPL10A and RPL10C, may fulfill the function of yeast RPL10 and, consequently, are all probably involved in translation.…”
Section: Discussionmentioning
confidence: 99%
“…3b) indicating that the structure of the RNA in vivo is very different from in vitro. Much of the weak correlation, in this instance, is likely due to the presence of intermolecular RNA-RNA interactions in the cellular environment, as part of 5.8S rRNA is known to base pair with 25S rRNA 24 (see the phylogenetic structure in Fig. 3c).…”
Section: Article Nature Communications | Doi: 101038/ncomms3971mentioning
confidence: 99%
“…(Yeast ribosomal proteins are evolutionarily conserved with A. thaliana and other eukaryotes 24 ). We identified several ribosomal proteins near H18-H20 (Fig.…”
Section: Article Nature Communications | Doi: 101038/ncomms3971mentioning
confidence: 99%